Pyrolysis of municipal plastic waste: article - Mohd Saidi, Nur Syafiqah; Alias, Rusmi (2019)
Since the over-used of plastic is becoming a major issue in the world nowadays, efforts of recycling the plastics into useful materials are being developed. One of the most common methods used in converting the plastic into valuable product is pyrolysis. This study aims to produce oil from the PET plastic bottles. The PET type of plastics is chosen as the raw material of the research since the plastic can be easily collected and recycled. The plastic slowly went through pyrolysis at four different temperatures of 300, 400, 500 and 600°C to produce the oil. At the first part of the study, the thermal degradation study was carried out with Thermogravimetric Analyser (TGA) from room temperature to 1000°C with heating rate of 10°C/min. The result from the TGA also is used to determine the content of moisture, volatile matter, fixed carbon and ash through proximate analysis and the appropriate range of temperature was determined. The pyrolysis process of the PET plastic in fixed bed reactor was done at the same condition in order to produce the solid, liquid and gas products. The highest yield of oil was produced at temperature of 400°C. The pyrolysis product was characterized by using FT-IR and GC-MS characterization techniques. Experimental results showed that pyrolysis could be an important method for the determination of the operating conditions and also an environmentally-friendly way for the transformation of the plastic wastes into valuable chemicals which later can be used as alternative fuel.